Studi Literatur: Tantangan dan Peluang Kepala Sekolah dalam Memimpin Inovasi Manajemen Kurikulum Berbasis Teknologi - Puspitasari, Ni Luh Gede Dian; Haeruddin, Haeruddin; Akhmad, Akhmad (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study is a literature review that explores the challenges and opportunities faced by school principals in leading technology-based curriculum innovation. In the digital era, educational institutions are under pressure to integrate technological advancements into curriculum management. School principals play a strategic role in facilitating this transformation, yet they often encounter significant barriers such as limited infrastructure, resistance to change among teachers, and lack of digital competence. This study aims to identify these issues while also highlighting the potential enablers of successful implementation, including policy support, access to online training, and cross-sector collaboration. Using a qualitative approach, the study analyzes and synthesizes findings from academic journals, books, research reports, and policy documents published between 2020 and 2025. Thematic analysis was used to extract core patterns related to leadership, digital curriculum management, and institutional change. The findings show that transformational and distributed leadership styles are essential in guiding schools through the integration of technology into teaching and learning processes. Furthermore, school principals are expected to create a collaborative and innovation-friendly school culture while continuously enhancing teachers’ digital competencies. The study recommends ongoing professional development and strategic partnerships as key factors in ensuring effective and sustainable digital curriculum innovation in schools.